Is Intensive Care Unit Admission Necessary After Removal of Mandibular Distraction Devices in Infants With Robin Sequence?. (March 2021) - Resnick, Cory M.; Caprio, Ryan; Evans, Faye; Park, Raymond
Objective: Intensive care unit (ICU) care is routinely required after the operation to initiate mandibular distraction osteogenesis (MDO) in infants with Robin sequence (RS). Many patients are also managed in the ICU after subsequent device removal. It is uncertain if ICU care, which is expensive and limited, is necessary after this second operation. The objective of this study was to evaluate the incidence of respiratory events following device removal. We hypothesized that respiratory events would be infrequent and non-ICU inpatient monitoring would be adequate. Design: This is a retrospective study of patients with RS from 2013 to 2018. Patients: Patients were included if they had MDO and distractor removal during the first year of life. Patients were excluded if they had a tracheostomy or remained intubated after distractor removal. Main Outcome Measure: Postoperative respiratory events. Results: Twenty-five (60% male) patients were included. Mean age and weight at distractor removal were 142 ± 79 days of life and 5.5 ± 1.1 kg. Mean apnea–hypopnea index after completion of distraction was 1.1 ± 1.5 events/hour. Two (8%) patients experienced postoperative respiratory events that required intervention. In 1 (4% of sample) of these, the event was deemed to have benefited from ICU-level care. Two variables were significantly associated with these events: congenital heart disease ( P = .020) and concomitant procedure performed during the same operation ( P = .020). Conclusions: Intensive care unit–level care is rarely needed after distractor removal in infants with RS. Intensive care unit admission should be considered in patients with congenital cardiac disease and when having multiple operations during the same anesthetic.